2019
DOI: 10.1038/s41419-019-2001-7
|View full text |Cite
|
Sign up to set email alerts
|

Cannabidiol promotes apoptosis via regulation of XIAP/Smac in gastric cancer

Abstract: According to recent studies, Cannabidiol (CBD), one of the main components of Cannabis sativa, has anticancer effects in several cancers. However, the exact mechanism of CBD action is not currently understood. Here, CBD promoted cell death in gastric cancer. We suggest that CBD induced apoptosis by suppressing X-linked inhibitor apoptosis (XIAP), a member of the IAP protein family. CBD reduced XIAP protein levels while increasing ubiquitination of XIAP. The expression of Smac, a known inhibitor of XIAP, was fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
75
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(76 citation statements)
references
References 28 publications
1
75
0
Order By: Relevance
“…There are also other studies where cancer cells were cultured with 10% FCS and treated with CBD or other synthetic CBD-like molecules. The results of these studies showed that CBD (5-20 μg/mL) reduced the viability of cancer cells and also had effects on other survival variables [6][7][8]16]. The cell lines used in these studies being different to the ones used in our study, could account for the different results observed.…”
Section: Limitationsmentioning
confidence: 56%
“…There are also other studies where cancer cells were cultured with 10% FCS and treated with CBD or other synthetic CBD-like molecules. The results of these studies showed that CBD (5-20 μg/mL) reduced the viability of cancer cells and also had effects on other survival variables [6][7][8]16]. The cell lines used in these studies being different to the ones used in our study, could account for the different results observed.…”
Section: Limitationsmentioning
confidence: 56%
“…CBD is known for its anticancer activity [ 16 ] and is the abundant phytocannabinoid in the IGB strain (50.7%, Supplementary Table S1 ). Hence, we also examined the effect of CB1 and CB2 IA on CBD activity.…”
Section: Resultsmentioning
confidence: 99%
“…We generated the mouse model of xenografted gastric cancer as previously described [ 30 ]. Briefly, AGS cells (10 7 cells) were subcutaneously injected into each mouse [ 34 , 35 ]. The mice were weighed twice a week.…”
Section: Methodsmentioning
confidence: 99%